Blod, sved og tårer - prodigier i romersk religion - Rasmussen, Susanne William (Religionsvidenskabeligt Tidsskrift, 1998)
Modern research has often viewed prodigies as weird and meaningless: either as the byproduct of ignorance, fear and mass hysteria - focusing on phychological aspects, or as calculating politicians' means of manipulating superstition - focusing on the possibility of fraud in political situations. This article is an attempt at presenting prodigies and their expiation as an important institution within official Roman religion and as a stable and effective means of sustaining a religious, political and social equilibrium in accordance with pax deorum and mos maiorum.